Risk Factors for Mortality of COVID-19 Patient Based on Clinical Course: A Single Center Retrospective Case-Control Study - Zhang, Jing; Wang, Zhihua; Wang, Xiong; Hu, Zhiquan; Yang, Chunguang; Lei, Ping (Frontiers in Immunology, 2021)
Background: Epidemiological, clinical characteristics and risk factors for mortality of COVID-19 patients have been studied, but the role of complement system, possible inflammatory and immune response mechanisms, and detailed clinical course, have not been well researched. Methods: In this single center, retrospective case-control study, we included all COVID-19 inpatients transferred or admitted to Wuhan Tongji Hospital from Jan 3 to Mar 30 2020 who had definite clinical outcomes (cured or deceased) with complete laboratory and radiological results. Clinical data were extracted from the electronic medical records, and compared between the cured and deceased patients. ROC curves were used to evaluate the prognostic value of the clinical parameters, and multivariable logistic regression analysis was performed to explore the risk factors for mortality. The correlation between the variables was evaluated by Pearson correlation analysis. Results: 208 patients were included in this study, 182 patients were cured and discharged, 26 patients died from COVID-2019. Most patients had comorbidities, with hypertension as the most common chronic disease (80; 38%). The most common symptoms at onset were fever (149; 72%), cough (137; 66%), and dyspnea (113; 54%). Elevated leucocytes, neutrophils, inflammatory biomarkers (CRP, ferritin, IL6, IL8, procalcitonin), PT, D-dimer, myocardial enzymes, BUN, decreased lymphocyte and subsets (T cells, Th cells, Ts cells, NK cells, T cells+B cells+NK cells), immunological factors (C3, C4) indicated poor outcome. PT, C3 and T cells were confirmed as independent prognostic factors for mortality by logistic regression models. IL6 and CPR were positively correlated with neutrophils, but negatively with lymphocytes and lymphocyte subsets except B cells. IL8 and ferritin were negatively related to T cells and Th cells. Positive associations exsited between C3 and T cells, Th cells, Ts cells, whereas no significant correlation between C4 and lymphocyte subsets. PT was found positively correlated with IL6, IL8 and CRP. Reverse correlations were explored between C3, C4 and PT, CK-MB, total bilirubin. Conclusions: T cells, C3 and PT were identified as independent prognostic factors for mortality. Activation of C3 and C4, dysregulation of lymphocyte subsets and cytokines, may lead to serious illness or even death after SARS-CoV-2 infection.